2021
DOI: 10.1039/d0tb02564j
|View full text |Cite
|
Sign up to set email alerts
|

Combination of mitochondria targeting doxorubicin with Bcl-2 function-converting peptide NuBCP-9 for synergistic breast cancer metastasis inhibition

Abstract: Distant organ metastasis is the main cause of death in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, the stronger the expression of Bcl-2, the higher the malignant degree of the tumor and the worse the biological behaviour of the tumor. Bcl-2, however, has been shown in more and more clinical studies to be associated with some favourable outcomes in breast cancer [12,13]. It was found by Melella et al [14], that estrogen can stimulate the expression of Bcl-2 in MCF-7 cancer cell line, confirming that the expression of Bcl-2 is regulated by estrogen, and the expression of this protein is mostly limited to ER-positive breast cancer cells.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the stronger the expression of Bcl-2, the higher the malignant degree of the tumor and the worse the biological behaviour of the tumor. Bcl-2, however, has been shown in more and more clinical studies to be associated with some favourable outcomes in breast cancer [12,13]. It was found by Melella et al [14], that estrogen can stimulate the expression of Bcl-2 in MCF-7 cancer cell line, confirming that the expression of Bcl-2 is regulated by estrogen, and the expression of this protein is mostly limited to ER-positive breast cancer cells.…”
Section: Discussionmentioning
confidence: 93%
“…We investigated whether the Bcl-2-dependent apoptosis induced by BFC1103 correlated with a change in the conformation of Bcl-2, converting its function from an antiapoptotic to a proapoptotic protein. We used a Bcl-2-BH3 domain antibody that specifically recognizes Bcl-2 with a changed conformation. Following treatment with BFC1103, the altered conformation of Bcl-2 was detected in MDA-MB-231/Bcl-2 cells (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Nur77 translocates from the nucleus to the mitochondria upon stimulation with certain compounds and initiates apoptosis. Nur77 interacts with Bcl-2, resulting in mitochondrial localization of Nur77 and induction of apoptosis. We discovered a 9-amino acid Nur77-derived Bcl-2 converting peptide (NuBCP-9), which is capable of mimicking the mechanistic and functional activities of Nur77. NuBCP-9 binds to the loop domain of Bcl-2, altering its phenotype to a prodeath protein by exposing its BH3 domain. As with many anticancer compounds, resistance has been reported to small molecule inhibitors of the Bcl-2 family of proteins. While most therapies are targeted to effectively inhibit primary tumors, there are hardly any reliable therapies for metastatic cancers. Because of this, metastasis accounts for up to 80% of cancer mortality.…”
mentioning
confidence: 99%
“…A Bcl-2-functional conversion peptide (NuBCP9, i.e., N9), derived from the orphan nuclear receptor Nur77, was also used with paclitaxel delivered by polylactic acid–polyethylene glycolpolypropylene glycol–polyethylene glycol [PLA-(PEG-PPG-PEG)] nanoparticles to synergistically treat breast cancer for enhanced therapy efficiency . Yang et al also used hydroxypropyl methacrylamide (HPMA) copolymers to construct a mitochondria-targeting peptide-modified doxorubicin (DOX-MPP) HPMA conjugate and a N9 peptide-loaded HPMA conjugate, respectively, through a pH-sensitive hydrazone bond and reductive environment-responsive disulfide bond for the combined use against metastatic breast cancer, which successfully inhibited 84% of lung metastasis . In our previous research, we also reported a kind of hybrid nanocomposites, which consisted of the internal large pore-sized MSNs and the external PAMAM dendrimers for coloading and sequentially delivering the N9 peptide and DOX to the mitochondria and nucleus for synergistically treating drug-resistant cancers .…”
Section: Introductionmentioning
confidence: 99%
“…6 Yang et al also used hydroxypropyl methacrylamide (HPMA) copolymers to construct a mitochondria-targeting peptide-modified doxorubicin (DOX-MPP) HPMA conjugate and a N9 peptideloaded HPMA conjugate, respectively, through a pH-sensitive hydrazone bond and reductive environment-responsive disulfide bond for the combined use against metastatic breast cancer, which successfully inhibited 84% of lung metastasis. 7 In our previous research, we also reported a kind of hybrid nanocomposites, which consisted of the internal large poresized MSNs and the external PAMAM dendrimers for coloading and sequentially delivering the N9 peptide and DOX to the mitochondria and nucleus for synergistically treating drug-resistant cancers. 8 However, the research on releasing the polypeptide/protein drugs at the targeted sites in a spatiotemporal controlled manner and combination treatment against resistant tumors with a medicinal compound in an enhanced way was rarely reported.…”
Section: Introductionmentioning
confidence: 99%